Frequencies of Apolipoprotein E Polymorphism in a Healthy Kurdish Population from Kermanshah, Iran - Vaisi-Raygani, Asad; Kharrazi, Hadi; Rahimi, Zohreh; Pourmotabbed, Tayebeh (Human biology, 2007)
The molecular polymorphism displayed by apolipoprotein E (APOE) has been listed as a risk factor for susceptibility to various disorders, such as those associated with lipid metabolism, arteriosclerosis, coronary artery disease (CAD), and Alzheimer disease. To evaluate the role of APOE genotypes as risk factors for Alzheimer disease, CAD, and atherosclerosis in the Kurdish population of Kermanshah, Iran, we studied the frequencies of APOE alleles *2, *3, and *4 and genotypes in 914 healthy Kurdish subjects (514 men and 400 women). The highest frequency of APOE in the Kurdish population was found for APOE*3 (87.87%). The APOE*2 and APOE*4 allele frequencies were 6.66% and 5.45%, respectively. Distribution of APOE genotypes and alleles was not significantly different between male and female subjects (p > 0.05). Interestingly, the order of the frequency of APOE alleles (*3 → *2 → *4) in the Kurdish population was quite different from that reported for most populations in the world (*3 → *4 → *2). The findings of the present study can be used to identify individuals with high risk of CAD and atherosclerosis and suggest a preventive measure to reduce their susceptibility.